A newly discovered Anaerococcus strain responsible for axillary odor and a new axillary odor inhibitor, pentagalloyl glucose. Issue 1 (14th May 2014) - Fujii, Takayoshi; Shinozaki, Junko; Kajiura, Takayuki; Iwasaki, Keiji; Fudou, Ryosuke
Abstract Skin surface bacteria contribute to body odor, especially axillary odor. We aimed to investigate anaerobic bacteria that had not been previously studied for axillary odor formation. A new anaerobic Anaerococcus sp. A20, that releases 3‐hydroxy‐3‐metyl‐hexanoic acid (HMHA, main component of axillary odor) from its glutamyl conjugate, was discovered from axillary isolates. This strain showed strong resistance to the antimicrobial agents, triclosan and 4‐isopropyl‐3‐methylphenol; therefore, we screened plant extracts that inhibit the A20 strain. We discovered that pentagalloyl glucose (PGG) extracted from the Chinese Gall plant exhibited both antibacterial and inhibitory activities against HMHA release by the A20 strain. As the excellent antibacterial activity and inhibitory effect of PGG against HMHA release were seen in vitro, we conducted an open study to evaluate the deodorant effects of PGG on axillary odor. The sensory tests on odor strength showed that application of the PGG solution could reduce axillary odors in vivo. Although there was a small change in axillary microbiota, the microbial count of A20 significantly reduced. These results strongly indicate PGG as a new innovative deodorant material that only affects odor‐releasing bacteria in the axillary microbiota.